1989
DOI: 10.1086/132589
|View full text |Cite
|
Sign up to set email alerts
|

The orbital inclination of A0620 - 00 measured polarimetrically

Abstract: The mass of the degenerate primary in A0620-00 is inferred from its spectroscopic mass function to be > 3.2 making it an excellent candidate for a black hole. The exact value of the mass depends on the orbital inclination. The inclination of a binary system can be determined from the shape of its Stokes parameter light curves if the linear polarization of the system varies as a function of orbital phase. We observed A0620-00 over one 8-hour binary period with the 4.5-m equivalent MMT. Its polarization in the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 7 publications
1
34
0
Order By: Relevance
“…4b). The quiescent optical (Dolan & Tapia 1989;Dubus et al 2008) and NIR (LIRIS) FLP clearly lie above the relation for interstellar dust, and so must have a different origin.…”
Section: A0620-00mentioning
confidence: 93%
See 4 more Smart Citations
“…4b). The quiescent optical (Dolan & Tapia 1989;Dubus et al 2008) and NIR (LIRIS) FLP clearly lie above the relation for interstellar dust, and so must have a different origin.…”
Section: A0620-00mentioning
confidence: 93%
“…Dolan & Tapia (1989) found that the optical (white light) FLP varied with the orbital phase in quiescence, with values of FLP ∼ 1.6-3.2 per cent. Dubus et al (2008) also measured FLP = 3.08 ± 0.04 per cent in V -band during quiescence but did not detect the orbital modulation.…”
Section: A0620-00mentioning
confidence: 97%
See 3 more Smart Citations